Ambient air pollution and pregnancy outcomes: a review of the literature - Srám, Radim J; Binková, Blanka; Dejmek, Jan; Bobak, Martin (Environmental health perspectives, 2005)
Over the last decade or so, a large number of studies have investigated the possible adverse effects of ambient air pollution on birth outcomes. We reviewed these studies, which were identified by a systematic search of the main scientific databases. Virtually all reviewed studies were population based, with information on exposure to air pollution derived from routine monitoring sources. Overall, there is evidence implicating air pollution in adverse effects on different birth outcomes, but the strength of the evidence differs between outcomes. The evidence is sufficient to infer a causal relationship between particulate air pollution and respiratory deaths in the postneonatal period. For air pollution and birth weight the evidence suggests causality, but further studies are needed to confirm an effect and its size and to clarify the most vulnerable period of pregnancy and the role of different pollutants. For preterm births and intrauterine growth retardation (IUGR) the evidence as yet is insufficient to infer causality, but the available evidence justifies further studies. Molecular epidemiologic studies suggest possible biologic mechanisms for the effect on birth weight, premature birth, and IUGR and support the view that the relation between pollution and these birth outcomes is genuine. For birth defects, the evidence base so far is insufficient to draw conclusions. In terms of exposure to specific pollutants, particulates seem the most important for infant deaths, and the effect on IUGR seems linked to polycyclic aromatic hydrocarbons, but the existing evidence does not allow precise identification of the different pollutants or the timing of exposure that can result in adverse pregnancy outcomes.
Keywords: novorozenec; Infant, Newborn; Female; Infant, Low Birth Weight; znečištění ovzduší; výsledek těhotenství; kojenecká mortalita; Humans; ženské pohlaví; Infant; Pregnancy; novorozenec s nízkou porodní hmotností; lidé; Air Pollution; kojenec; Pregnancy Outcome; těhotenství; Infant Mortality